Interaction between phosphoribosyltransferase and purified histidine tRNA from wild type Salmonella typhimurium and a derepressed hisT mutant strain. - Deeley, R G (1975)
We have examined the interaction between phosphoribosyltransferase and purified tRNA-His from the wild type strain of Salmonella typhimurium, LT-2, and the histidine regulatory mutant hisTl504. Histidyl-tRNA from the mutant strain functions normally in protein synthesis but is defective in its role in the repression mechanism of the histidine operon. Phosphoribosyltransferase has been suggested as a possible aporegulator for this operon and as such might be expected to interact abnormally with tRNA-His from hisT1504. In these studies we have been unable to detect any difference between the affinities of phosphoribosyltransferase for tRNA-His from LT-2 or hisT1504, and thus we conclude that if the complex between phosphoribosyltransferase and histidyl-tRNA does function in regulation, the defect in the hisT1504 mutant must influence the interaction of the complex with some other regulatory element.